Changes in functional connectivity associated with facial expression processing over the working adult lifespan. (June 2022) - Murray, Thomas; O'Brien, Justin; Sagiv, Noam; Kumari, Veena
Abstract: The recognition of negative emotions from facial expressions is shown to decline across the adult lifespan, with some evidence that this decline begins around middle age. While some studies have suggested ageing may be associated with changes in neural response to emotional expressions, it is not known whether ageing is associated with changes in the network connectivity associated with processing emotional expressions. In this study, we examined the effect of participant age on whole-brain connectivity to various brain regions that show connectivity during emotion processing, namely, the left and right amygdalae, medial prefrontal cortex (mPFC), and right posterior superior temporal sulcus (rpSTS). The study involved healthy participants aged 20–65 years who completed an implicit affect processing task involving facial expressions displaying anger, fear, happiness, and neutral expressions during functional magnetic resonance imaging (fMRI). Participants were also tested on recognition accuracy during an emotion labelling task. We found that participant age was negatively associated with connectivity between the left amygdala and voxels in the left occipital pole; between the rpSTS and voxels in the orbitofrontal cortex; and between the mPFC and cingulate cortex and left insular cortex. Furthermore, these effects were due to a greater age-related decline in brain connectivity for negative expressions compared to happy and neutral expressions. There was, however, no significant relationship between age and emotion recognition accuracy (though in the expected direction), and between connectivity strength and emotion recognition accuracy. Together, these results provide evidence for a specific age-related decline in the neural processing of negative emotions, and could suggest that changes in underlying network connectivity over the working adult lifespan might occur before any marked decline in the recognition of the emotion.